Influence of angle kappa and angle alpha on visual quality after implantation of multifocal intraocular lenses. Issue 9 (September 2019) - Fu, Yana; Kou, Jiaojiao; Chen, Dongjie; Wang, Dandan; Zhao, Yinyin; Hu, Man; Lin, Xiaolei; Dai, Qi; Li, Junhua; Zhao, Yun‐e
Abstract : Purpose : To assess the influence of angle kappa (κ) and angle alpha (α) on visual quality after multifocal intraocular lens (IOL) implantation. Setting : Eye Hospital, Wenzhou Medical University, Wenzhou, Zhejiang, China. Design : Prospective case series. Methods : Patients with cataract had phacoemulsification with TECNIS Symfony IOL implantation. The preoperative angle κ and angle α were measured using the iTrace device. Distance, intermediate, and near visual acuities were recorded 3 months postoperatively. The Optical Quality Analyzing System was used to measure the objective scatter index (OSI), modulation transfer function (MTF) cutoff frequency, and Strehl ratio. A patient questionnaire was also administered. Results : The study comprised 29 patients (57 eyes). Monocularly, the mean postoperative logarithm of the minimum angle of resolution (logMAR) uncorrected distance, intermediate, and near visual acuities were 0.03 ± 0.09 (SD), 0.05 ± 0.11, and 0.11 ± 0.09, respectively. The mean postoperative logMAR corrected distance, distance‐corrected intermediate, and distance‐corrected near visual acuities were −0.01 ± 0.05, 0.04 ± 0.09, and 0.11 ± 0.08, respectively. The mean OSI, MTF cutoff, and Strehl ratio were 1.27 ± 0.84, 32.03 ± 10.80 cycles per degree, and 0.17 ± 0.05, respectively. The OSI ( r = 0.398, P = .005), MTF ( r = −0.437, P = .002), and Strehl ratio ( r = −0.419, P = .003) values were significantly correlated with angle κ. There was no correlation with angle α. Conclusions : Angle κ affected the objective visual quality multifocal after IOL implantation. The decision to implant a multifocal IOL should be carefully considered for patients with a large angle κ.